PERAN PANGKALAN UTAMA TNI ANGKATAN LAUT V SURABAYA DALAM REKONSTRUKSI PEMBANGUNAN PERUMAHAN DI LOKASI BENCANA ALAM GEMPA BUMI DAN IMPLIKASINYA TERHADAP KETAHANAN WILAYAH (Studi di Dusun Paten Desa Srihardono Kecamatan Pundong Kabupaten Bantul Provinsi D.I.Yogyakarta - , Nur Agus Arifin ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to determine the role of the Navy Main Base V (Lantamal V) Surabaya in housing reconstruction in earthquake locations in the hamlet village of Paten Srihardono Pundong sub district of Bantul Yogyakarta. In addition, this study also will determine the factors that become the constraints and the impact and implications of the role of the Navy Main Base V (Lantamal V) Surabaya to regional resilience. Navy Role in housing reconstruction in addition to reference to the Law of the Republic of Indonesia Number 34 Year 2004 on Armed Forces of Indonesia has the main tasks undertaken by Operation Military Other Than War (OMOW) that help cope with natural disasters (Article 7), also encouraged a sense of humanity, where human beings with one another help each other to solve social problems. The method used in this study is a combination of qualitative and descriptive statistics by describing the Navy's role in the reconstruction of housing development residents. The instrument used in data collection by distributing questionnaire to 50 respondents at random. As an amplifier analysis used the interview data that are indepth interviews and is free. To avoid accidental data, then informant interviews with 4 people. To get the data questioner, interview and find out the actual state of the Paten hamlet used observational methods. Other data as a deepening of the material, the use of secondary data in the form of literature study of literature books and documents related to discussion. From the findings in the field, Role Lantamal V Surabaya build earthquake-resistant housing type 45 number 145 units in village Srihardono for using, ie 113 units for the hamlet of Patents and 32 units divided by another hamlet. The impact of the reconstruction of housing development for villagers Patents can raise the passion of the spirit of life, so that they can conduct its activities back in a few sectors, particularly in the economic sector. Other effects that occur are growing jealousy of other villagers. Reconstruction of housing development significantly influence Resilience areas include: aspects of ideology with a donation of 17%, political aspects 22%, economic aspects 40.1% and security aspects 21%.